Identification of Bioactive Compounds and Antibacterial Activity of Sea Cucumber, Holothuria (Halodeima) atra Jaeger 1833 Flesh Extract from Kalasey Coastal Waters, Minahasa District - Mewengkang, Theresia Tessa; Lintang, Rosita Anggreiny; Losung, Fitje; Sumilat, Deiske Adeliene; Lumingas, Lawrence J. L (Jurnal Ilmiah Platax, 2022)
Sea cucumbers are one of the marine biotas that contain bioactive compounds that have the potential as antibacterial ingredients. The purpose of this study was to perform antibacterial testing on fractions of the extract of the sea cucumber H. atra meat and to conduct a zoochemical analysis to determine the content of bioactive compounds that can inhibit bacterial growth. Antibacterial testing using disc diffusion method against Staphylococcus aureus and Escherichia coli bacteria. The results showed that the methanol extract of sea cucumber flesh could inhibit the growth of both types of test bacteria. In antibacterial testing for S. aureus, the ethyl acetate fraction was 11.8 mm, the n-hexane fraction was 7 mm, and the methanol fraction was 8.6 mm, while for E. coli the ethyl acetate fraction was 10.88 mm, the n-hexane fraction was 7 mm, and 8.6 mm methanol fraction. The compounds contained in the ethyl acetate fraction of sea cucumber H. atra flesh extract are alkaloids, flavonoids, steroids, and saponins which are compounds that can inhibit bacterial growth with their respective working mechanisms.Keywords: Disc diffusion, Extraction, Fractionation, Sea cucumber (H.atra), Zoo-chemical, AbstrakTeripang merupakan salah satu biota laut yang memiliki kandungan senyawa bioaktif yang berpotensi sebagai bahan antibakteri. Tujuan penelitian ini melakukan pengujian antibakteri pada fraksi-fraksi dari ekstrak daging teripang H. atra dan melakukan analisis zookimia untuk mengetahui kandungan senyawa bioaktif yang dapat menghambat pertumbuhan bakteri. Pengujian antibakteri menggunakan metode difusi cakram terhadap bakteri Staphylococcus aureus dan Escherichia coli. Hasil penelitian menunjukkan bahwa ekstrak metanol daging teripang memiliki dapat menghambat pertumbuhan kedua jenis bakteri uji. Pengujian antibakteri terhadap S. aureus fraksi etil asetat sebesar 11,8 mm, fraksi n-heksan 7 mm, dan fraksi metanol 8,6 mm sedangkan untuk bakteri E. coli fraksi etil asetat sebesar 10,88 mm, fraksi n heksana 7 mm, dan fraksi metanol 8,6 mm. Kandungan senyawa yang yang terkandung dalam fraksi etil asetat ekstrak daging teripang H. atra yaitu senyawa alkaloid, flavonoid, steroid, dan saponin yang merupakan senyawa yang dapat menghambat pertumbuhan bakteri dengan mekanisme kerja masing-masing.Kata KunciÂ  : Difusi cakram, Ekstraksi, Fraksinasi , Teripang (H. atra), Zoo-kimia,